Certain solitons on $α$-cosymplectic manifolds - Sardar, A.; Sarkar, A. (Carpathian Mathematical Publications, 2024)
In the present paper, we characterize some solitons such as $η$-Einstein soliton, $η$-Yamabe soliton and Ricci-Yamabe soliton on $α$-cosymplectic manifolds. Furthermore, we characterize $3$-dimensional $α$-cosymplectic manifolds with gradient Ricci-Yamabe soliton. Finally, we construct an example.